The Effect of Giving Modified Yellow Pumpkin Soybean Noodles and Tuna Fish on Body Weight and Height of Wasting Toddlers in Medan City - Nasution, Muharmansyah; Sudaryati, Etti; Lubis, Zulhaida (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study used a quasi-experimental design with a before and after treatment design using a control group and a treatment group with the aim of determining the effect of giving modified soy pumpkin noodles and tuna fish on body weight and height in 18 wasting toddlers in Medan City. The data collection method was food recall before and after treatment, and measuring body weight and height in the treatment group and the control group was given 100 grams of modified soy pumpkin noodles and tuna fish for 30 days from November to December 2023. The results of the study showed an increase After treatment, the z score for BB/TB increased, the post test results between the control group and the treatment group were independent T test results (p=0.001).